Comprendre les ressorts des pratiques organisationnelles en matière de prévention des risques psychosociaux par les acteurs de l’entreprise - Sabrina Rouat; Victor Troyano; Bruno Cuvillier; Marc-Eric Bobillier-Chaumon; Philippe Sarnin (Perspectives Interdisciplinaires sur le Travail et la Santé)
The scientific literature points to an individualization of psychological health issues at work that is hindering efficient prevention. Using a mixed method, we sought to verify whether people in organizations noticed the described trend in the individualization of health issues. A survey was conducted with 137 people (staff representatives and managers) about the importance they attributed to six factors that influenced the emergence of psychosocial risks. The results showed that the perceived weight of the “personal difficulties” factor was significantly lower than those of “work pressure” and “internal group issues.” The individual perception of factors influencing psychosocial risks therefore seems to be driven more by “working condition challenges” than “personal challenges.” The collective interviews furthermore showed how social relations impacted organizational practices.